‘A Different Voice’ in Peer Feedback: Gender Specificity in Students’ Willingness to Provide Peer Feedback - Dominique-Esther Seroussi; Yehuda Peled; Rakefet Sharon; Nathan Rothschild; Osnat Halperin Barlev; Eyal Weissblueth; Gal Harpaz (Education Sciences, 2023)
In the context of the efforts to reach equity in the classroom, peer feedback (PFB) is used, among other participative learning methods, as it is considered to minimize gender differences. Yet, recent studies have reported gender discrepancies in students’ willingness to provide feedback to their peers. Building on Gilligan’s theory of moral development, we tried to refine the source of this difference. We conducted a semi-experimental study during which education students of both genders performing a PFB activity in a face-to-face course were asked to fill out a questionnaire. This allowed us to estimate the link between, on the one hand, the comfort in providing PFB and the willingness to provide PFB, and on the other hand, personal characteristics like self-esteem, self-efficacy, and empathic concern, and intellectual characteristics like self-efficacy in the learned discipline and the proficiency to write and understand feedback. The linear regression analysis of 57 students’ answers to the questionnaire did not reveal gender differences in comfort in providing PFB and willingness to do so, but showed that the comfort in providing PFB was linked to cognitive proficiency in students of both genders, whereas the willingness to provide PFB was independent of any other variables in men and linked to self-esteem, empathic concern, and comfort in providing feedback in women. This result indicates a differential sensitivity to social factors in male and female students, aligning with Gilligan’s model of women’s ‘ethics of care’. Possible applications in education would be the use of PFB to train women in self-esteem or, inversely, the improvement of psychological safety in PFB exercises in groups including female students.